The Effect of Ease of Application and Ease of Payment in Online Sales to Increase Sales - Arman Syah Putra; Dismita Citra Dewi; Hendi Kariyanto; Murlita; Risdianto (Publisher Cv. Inara, 2021)
The background of this research is to find out how to increase sales by using a new method, namely the online sales method. With this method, the writer wants to know what variables can affect the sales increase variable. Therefore, the variables raised in this writing are: the ease of using the application variable and the convenience variable in paying for the online purchase system with these variables it is known what variables influence in order to improve sales of a product online. The method used in this study is to use quantitative methods using survey tools. Carried out to 100 sellers who sell their products online, therefore the results of the data obtained will be real data in the field so that they can find out whether these variables affect the increasing variables n rate of sales made online. The problem raised in this study is how to determine a variable that can affect other variables. The variables raised in this study are the variable ease of using the application and the variable convenience in your payment to increase sales made online. The purpose of this study is to find out how to increase sales of a product or service with an online sales method system. Therefore, the author wants to know what variables affect online sales in order to increase sales of a product or service.